Unraveling the Cascading Effects: Banking Frauds, Performance, and Exchange Rate Volatility Dynamics - Sen, Binata Rani; Minghui, Jiang (Archives of Business Research, 2025)
The link between banking fraud, banking sector performance, and exchange rate fluctuations has significant implications worldwide, notably affecting countries like Bangladesh. Over the past two decades, Bangladesh has grappled with major banking frauds that have eroded trust and stability in its financial sector. This study explores the interconnectedness of banking fraud, banking performance, and exchange rate volatility in Bangladesh from 2000 to 2023. Utilizing Cressey's Fraud Triangle Theory and statistical models like GARCH and VECM, researchers found that the fraud cases and the personnel engaged in fraud negatively impact bank performance. Interestingly, the total monetary value of fraud cases had a positive influence. Furthermore, the study revealed that banking performance influenced Bangladesh's currency fluctuations against various trading partners positively, except for certain currencies like the Pound Sterling. The findings underscore the importance of enhancing internal controls to mitigate fraud, improve banking performance, and stabilize exchange rate dynamics in Bangladesh.